Cover Image, Volume 19, Issue 9. Issue 9 (23rd August 2017) - Blundell, John; Finlayson, Graham; Axelsen, Mads; Flint, Anne; Gibbons, Catherine; Kvist, Trine; Hjerpsted, Julie B.
Abstract : The cover image, by John Blundell et al., is based on the Original Article Effects of once‐weekly semaglutide on appetite, energy intake, control of eating, food preference and body weight in subjects with obesity, DOI: 10.1111/dom.12932 Abstract : The cover image, by John Blundell et al., is based on the Original Article Effects of once‐weekly semaglutide on appetite, energy intake, control of eating, food preference and body weight in subjects with obesity, DOI: 10.1111/dom.12932